Asia Pacific Business Process Management First Asia Pacific Conference, AP-BPM 2013, Beijing, China, August 29-30, 2013. Selected Papers - Song, Minseok; Wynn, Moe Thandar; Liu, Jianxun; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book constitutes the proceedings of the First Asia Pacific Conference on Business Process Management held in Beijing, China, in August 2013. In all, 19 contributions from seven countries were submitted. Following an extensive review process by an international Program Committee, seven full papers and one short paper were accepted for publication in this book and presentation at the conference. In addition, a keynote by Wil van der Aalst is also included.
Process Cubes: Slicing, Dicing, Rolling Up and Drilling Down Event Data for Process Mining -- APQL: A Process-Model Query Language -- BPEL Similarity $1 (BA Metric Based on Activity Constraint Graphs -- Process Model Storage Solutions: Proposition and Evaluation -- Clustering and Operation Analysis for Assembly Blocks Using Process Mining in Shipbuilding Industry -- DTMiner: A Tool for Decision Making Based on Historical Process Data -- Process Discovery by Synthesizing Activity Proximity and User$1 (Bs Domain Knowledge -- A Methodological Evaluation of Business Process Compliance Management Frameworks -- Improvement of Patient Safety in u-Hospital: A Pattern-Based Approach for Handling Patients$1 (BAbnormal Situations.s
Keywords: Computer science; Information technology; Business -- Data processing; Data mining; Application software; Computer Science; Computer Appl. in Administrative Data Processing; IT in Business; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery; Electronic books